In Silico Analysis of Momordica charantia L. as Antidiabetic Agents of GSK-3β Receptors and It's Antioxidant Activity - Pramesthi, Asri Dwi Endah Dewi; Khairunnisa, Khairunnisa; Zuliet, Aurelia Nabilla; Putri, Melani Pebriana; Kustiawan, Paula Mariana (Pharmacon: Jurnal Farmasi Indonesia, 2025)
Diabetes mellitus is included in the group of degenerative diseases with the highest incidence rate globally. This study was conducted to evaluate the potential of bioactive compounds contained in bitter melon (Momordica charantia L.) as antidiabetic and antioxidant agents using an in silico approach. The methods used include molecular docking simulations, pharmacokinetic and toxicological  analyses were carried out using Absorption, Distribution, Metabolism, Excretion, and Toxicology parameters as well as drug suitability tests based on the Lipinski rule of five. The test results showed that bitter melon juice obtained an IC50 of 63.18 μg/ml while vitamin C as a comparison obtained an IC50 of 7.60 μg/ml. The docking results show that the Kaemferol compound has the highest binding affinity (-6.64 Kcal/mol), Quercetin (-6.28 Kcal/mol) and Charantoside I (6.07 Kcal/mol) have stable binding energy, the interaction of charantin, quercetin, kaemferol and charantoside I residues is similar to native ligands such as Valine 135, Cysteine 199, Valine 70 and Lysine 85. Based on the ADMET profile results, the quercetin and kaemferol compounds have high absorption, Caco-2 permeability which supports oral bioavailability, and do not show the ability to penetrate the blood-brain barrier, which indicates safety for the central nervous system, as well as low AMES toxicity and hepatotoxicity. As the conclusion, kaempferol and quercetin compounds have  the potential as GSK-3β inhibitors. Antioxidant activity of bitter melon juice and vitamin C are categorized as strong. Further  research regarding the mechanism of action of Momordica charantia L. as an alternative therapeutic agent in the management of type  2 diabetes is needed.